Performance evaluation of line scanning method in proton therapy. (June 2019) - Azuma, Y; Tateoka, K
Abstract: Proton therapy system (Sumitomo Heavy Industries, Ltd.) in Sapporo Teishinkai Hospital consists of a cyclotron, a rotating gantry and a multi-purpose nozzle. This nozzle can irradiate both wobbler beam and line scanning beam. Performance of line scanning was evaluated in this study. The authors investigated for items related to the beam delivery. Dose linearity was investigated with a water phantom and a large parallel plate chamber with several dose rates. For evaluation of irradiation time precision, a solid water phantom and the large parallel plate chamber were used. Furthermore, several spot patterns were measured by Scintillator/CCD camera system for the estimation of beam position. Dose linearity is found with less than 1.8 % error with varying conditions. Regarding irradiation time, error is also confirmed with less than about 1.4 % in this measurement. Beam position accuracy and beam size constancy is also precise enough to be used in clinical use. In conclusion, it is found that results in this study are good enough for treatment.